Agricultural Trade Between the Philippines and the US: Status, Issues and Prospects - Liborio S. Cabanilla (Philippine Institute for Development Studies (PIDS), 2006)
The paper describes the environment under which RP-US agricultural trade currently operates. It also highlights key issues affecting current trade flows between the Philippines and the US, and provides background information vital for future bilateral agricultural negotiations with the U.S. Further to this, it shows that two major factors will determine the prospective net effects of a RP-US FTA on Philippine agriculture. First, the effects on exports will depend on the extent of US reduction of NTBs, particularly on mangoes, carrageenan, and canned tuna. Second, Philippine imports from the US will depend on its willingness to reconsider position, particularly on rice and corn. On this count, it must be noted that rice is an important wage good, and corn is a key livestock feed ingredient. Moreover, the advent of an FTA with the US should be a good reason to get Philippine agriculture better organized, in terms of policy and institutional support.
Keywords: 330; liberalization; market access; agricultural trade; US agriculture support programs; domestic support programs; nontariff barriers; border controls; Internationale Wirtschaftsbeziehungen; Freihandelszone; Agraraußenhandel; Handelsliberalisierung; Nichttarifäre Handelshemmnisse; Philippinen; USA